Mentality and thought : north, south, east and west - Durst-Andersen, Per; Lange, Elsebeth F. (Copenhagen Business School Press ; Distribution, North America, International Specialized Book Services, 2010)
"Mentality and Thought - North, South, East and West presents the reader with an informed pluri-disciplinary discussion of the concept of mentality, its relevance and its interconnection with culture past and present, on the one hand, and cognition and mental frames on the other. The exploration is one of both theoretical depth and socio-historical width, each paper providing its own synthetic combination of conceptual and empirical analysis."--Jacket